2002
DOI: 10.1007/s00134-002-1379-2
|View full text |Cite
|
Sign up to set email alerts
|

Keeping central venous lines open: a prospective comparison of heparin, vitamin C and sodium chloride sealing solutions in medical patients

Abstract: Local anticoagulation of intermittently used central venous catheters prolongs catheter patency. High-dose (5000 IU/ml) heparin solution is a useful anticoagulant for this purpose, while vitamin C solution does not prolong catheter patency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
2
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 15 publications
0
40
2
7
Order By: Relevance
“…Bibliography analysis of identified reference articles also allowed the inclusion of another study, thus nine studies were considered for critical appraisal: eight RCT (2,6,9,(11)(12)(13)(14)16) and one cohort study (10) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Bibliography analysis of identified reference articles also allowed the inclusion of another study, thus nine studies were considered for critical appraisal: eight RCT (2,6,9,(11)(12)(13)(14)16) and one cohort study (10) .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, there is no evidence in the literature that the concentration of heparin alone is related to improved permeable CVC rates, assuming a balance between effectiveness and safety of the patient (10) . However, the systemic effects of the use of heparin and the development of heparin-induced thrombocytopenia may constitute a problem (6) . Despite the potential benefits of saline solution, the change in clinical practice for a normal saline solution has not been widely suggested in the literature for the whole typology of patients and CVC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of strategies to reduce the incidence of CRB have been tried, including the use of strict hygienic measures, antibiotic-impregnated catheters, eradication of Staphylococcus aureus nasal carriage and prophylactic antibiotic ointment on the exit site [7]. Taurolidine and heparin, which can reduce the incidence of CRB, are often used as a solution to prevent bacteremia in patients who need a central catheter, as with hemodialysis, cancer and parenteral nutrition, as well as in the ICU [8,9,10,11]. It has been suggested that heparin, the most common catheter lock in clinical practice, may be abandoned because spilling into the bloodstream may expose patients to the risk of bleeding [12].…”
Section: Introductionmentioning
confidence: 99%